Binder-free ZSM-35 catalyst as well as preparation method and application thereof
The silicon source, aluminum source, alkali source, pore reamer and water are mixed uniformly by the binder-free method, extruded and molded, and hydrothermal crystallization is carried out to produce an efficient and suitable for industrial production, which solves the problems of low catalyst activity and poor mechanical strength in the prior art.
Patent Information
- Application Number
- CN202411891334.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-01
AI Technical Summary
The existing ZSM-35 catalyst needs to be added to the binder during the molding process, resulting in low catalyst activity, poor mechanical strength, and is not conducive to industrial production.
By mixing the silicon source, aluminum source, alkali source, pore reamer and water evenly, removing part of the solvent, extruding and molding, hydrothermal crystallization is carried out to prepare a binder-free ZSM-35 catalyst.
It realizes efficient preparation of binder-free ZSM-35 catalyst, improves catalytic activity and mechanical strength, and is suitable for factory-scale production.
Smart Images

Figure CN119733553A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of skeletal isomerization catalysts, and in particular to a binder-free ZSM-35 catalyst and a preparation method and application thereof. Background Art
[0002] As an important fine chemical product, isoolefins are increasingly used in industrial production. There are many methods for producing isoolefins, among which the skeletal isomerization of normal olefins is currently the most promising industrial technology. Among the catalysts for skeletal isomerization of olefins, molecular sieves are increasingly attracting attention as a class of excellent catalysts with high selectivity and high yield. Olefin skeletal isomerization reactions are usually carried out on acidic catalysts, among which molecular sieves with ten-membered rings show excellent catalytic performance due to their shape selectivity. ZSM-35 molecular sieve has a FER topological structure and a unique pore structure with one-dimensional ten-membered ring channels (0.42nm×0.54nm) and one-dimensional eight-membered ring channels (0.35nm×0.48nm). It is often studied as a catalyst for skeletal isomerization of olefins. At present, ZSM-35 has been proven to be the best catalyst for the skeletal isomerization of normal butenes, and has been industrialized. However, catalyst powders are inconvenient in practical applications due to their small particle size. They have weaknesses such as difficulty in recycling, easy deactivation and aggregation, so they need to be molded in advance. It is generally necessary to add a binder during the molding process. However, the binder is generally an inert component. The addition of the binder actually has a "diluting" effect on the active center of the molecular sieve, which increases the actual reaction space velocity and accelerates the deactivation of the catalyst. In addition, the binder has a certain pore blocking effect on the molecular sieve, which affects the diffusion performance, and ultimately leads to poor catalyst stability.
[0003] The zeolite particles of the binder-free zeolite molecular sieve do not contain a binder or only contain a small amount of binder, have a high zeolite content, and therefore have a larger effective available surface and better catalytic performance. Invention patent CN109701606A discloses a skeletal isomerization catalyst, a preparation method and its use, using one or at least one powder of a molecular sieve with a ten-membered ring structure as a seed, the seed and the binder are mixed and molded to obtain a precursor, the precursor converts the binder component into a molecular sieve through a hydrothermal reaction to obtain a binder-free molecular sieve, and the binder-free catalyst is obtained after ammonium exchange and calcination. The catalyst obtained by this method has poor strength and is difficult to achieve industrialization. Invention patent CN114713278A discloses a preparation method of a fully crystalline ZSM-35 molecular sieve and its application in olefin isomerization reaction, 75% to 90% of ZSM-35 molecular sieve raw powder, 9 to 25% silicon oxide, 0.15 to 1% aluminum compound, which is obtained by high temperature crystallization for a certain period of time in the atmosphere of the template agent. This solution still uses a large amount of ZSM-35 molecular sieve to participate in the crystallization process, which increases production costs.
[0004] Therefore, it is necessary to develop a binderless ZSM-35 catalyst with simpler process, better performance and better suitability for industrialization. Summary of the invention
[0005] In view of this, the present invention provides a binder-free ZSM-35 catalyst and its preparation method and application, which mainly solves the problems that the ZSM-35 molecular sieve catalyst prepared by the prior art has low activity after molding, poor mechanical strength, and is not conducive to industrial production. The present invention is to mix a silicon source, an aluminum source, an alkali source, a pore expander and water evenly, then remove part of the solvent to obtain a dry base, and then extrude the obtained dry base into a mold, and crystallize it in a template solution for a period of time to obtain a binder-free ZSM-35 catalyst. The binder-free ZSM-35 catalyst prepared by the present invention has better olefin conversion rate and selectivity than the catalytic effect of a conventional ZSM-35 catalyst under the same reaction conditions, and is suitable for factory-scale production.
[0006] A method for preparing a binder-free ZSM-35 catalyst comprises the following steps:
[0007] (1) mixing a silicon source, an aluminum source, an alkali source, a pore-enlarging agent and water uniformly to obtain a catalyst precursor I;
[0008] (2) removing part of the solvent from the catalyst precursor I to obtain a catalyst precursor II having a dry weight of 40 to 60%;
[0009] (3) Extruding the catalyst precursor II into a shape and drying it to obtain the catalyst precursor III;
[0010] (4) adding the catalyst precursor III to the template solution, and sequentially performing hydrothermal crystallization, filtering, washing, drying, and calcining to obtain a binder-free Na-type ZSM-35 catalyst;
[0011] (5) The binder-free Na-type ZSM-35 catalyst is exchanged with an ammonium salt aqueous solution, washed to neutrality, dried, and calcined to obtain a binder-free ZSM-35 catalyst.
[0012] Preferably, the silicon source in step (1) includes at least one of silica sol, C-type silica gel, and white carbon black, the aluminum source includes at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, pseudo-boehmite, and aluminum chloride, the alkali source includes sodium hydroxide, and the pore expanding agent includes any one of methyl cellulose, sesbania powder, polyethylene glycol, activated carbon, and starch.
[0013] Preferably, the silicon source, aluminum source, alkali source and water in step (1) are in the ratio of SiO2:Al2O 3:The pore-enlarging agent is mixed in a molar ratio of Na2O:H2O=40-90:1:4.0-15.0:500-2000, and the added amount of the pore-enlarging agent is 1-10wt% of SiO2.
[0014] Preferably, the template in step (4) is an amine compound, and the template includes at least one of pyrrolidine, ethylenediamine, cyclohexylamine, and pyridine. The concentration of the template solution is 3 to 15%, and the solid-liquid ratio of the catalyst precursor III to the template solution is 1:5 to 25.
[0015] Preferably, the crystallization temperature in step (4) is 150-190° C., and the crystallization time is 48-108 h.
[0016] Preferably, in step (5), the system temperature during the exchange with the ammonium salt aqueous solution is 40 to 90° C., and the exchange time is 1 to 6 hours.
[0017] Preferably, in the method, the drying conditions are 100-150° C. for 6-10 hours, and the roasting conditions are 450-600° C. for 4-8 hours.
[0018] The present invention also provides a binder-free ZSM-35 catalyst prepared according to the method and application of the ZSM-35 catalyst in hydrocarbon conversion.
[0019] Preferably, the ZSM-35 catalyst is used in olefin skeletal isomerization reaction.
[0020] Preferably, the reaction temperature is 250-350°C and the space velocity is 1-7h -1 .
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention adds a pore-enlarging agent to the catalyst precursor I, thereby reducing the molecular diffusion resistance and improving the catalytic activity.
[0023] The present invention can synthesize the ZSM-35 molecular sieve catalyst without adding molecular sieve as a seed crystal for induction during hydrothermal crystallization.
[0024] The present invention does not add a binder during the molding stage, thereby reducing the influence of the binder on the performance of the ZSM-35 molecular sieve catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 1 of the present invention.
[0026] Figure 2 It is a SEM picture of the ZSM-35 catalyst prepared in Comparative Example 1 of the present invention.
[0027] Figure 3 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 2 of the present invention.
[0028] Figure 4 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 3 of the present invention.
[0029] Figure 5 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 4 of the present invention.
[0030] Figure 6 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 5 of the present invention.
[0031] Figure 7 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 6 of the present invention.
[0032] Figure 8 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 7 of the present invention.
[0033] Fig. 9 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 8 of the present invention.
[0034] Fig.10 This is a SEM image of the binder-free ZSM-35 catalyst prepared in Example 9 of the present invention. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a binder-free ZSM-35 catalyst, comprising the following steps:
[0036] (1) mixing a silicon source, an aluminum source, an alkali source, a pore-enlarging agent and water uniformly to obtain a catalyst precursor I;
[0037] (2) removing part of the solvent from the catalyst precursor I to obtain a catalyst precursor II having a dry weight of 40 to 60%;
[0038] (3) Extruding the catalyst precursor II into a shape and drying it to obtain the catalyst precursor III;
[0039] (4) adding the catalyst precursor III to the template solution, and sequentially performing hydrothermal crystallization, filtering, washing, drying, and calcining to obtain a binder-free Na-type ZSM-35 catalyst;
[0040] (5) The binder-free Na-type ZSM-35 catalyst is exchanged with an ammonium salt aqueous solution, washed to neutrality, dried, and calcined to obtain a binder-free ZSM-35 catalyst.
[0041] The present invention forms a colloidal solution by mixing a silicon source, an aluminum source, an alkali source, a pore expander and water in a certain ratio, and after removing part of the solvent and drying the extruded strips, the silicon aluminum source material will gradually react to form a polymer of silicon aluminum oxide, and the pore expander will be wrapped in the polymer of silicon aluminum oxide; the template solution is added and placed in an autoclave for hydrothermal crystallization, and at a certain temperature and pressure, the silicon aluminum polymer in the reaction system depolymerizes and rearranges under the action of OH- ions to form a crystal nucleus, and the crystal nucleus is rearranged around the hydrated cation to form a polyhedron, and these polyhedrons are further polymerized, connected to form crystals, and finally converted into the crystalline structure of ZSM-35. In this process, the template agent will be wrapped in the framework of the molecular sieve to form a specific pore structure, and the pore expander will also be wrapped inside the crystal, and can be removed in the subsequent washing and drying process, leaving a larger pore, and improving the catalytic activity of the ZSM-35 catalyst.
[0042] In some embodiments of the present invention, the silicon source in step (1) includes at least one of silica sol, C-type silica gel, and white carbon black, the aluminum source includes at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, pseudo-boehmite, and aluminum chloride, the alkali source includes sodium hydroxide, and the pore expanding agent includes any one of methyl cellulose, sesbania powder, polyethylene glycol, activated carbon, and starch.
[0043] In some embodiments of the present invention, the silicon source, aluminum source, alkali source, and water in step (1) are in the form of SiO2:Al2O 3: The molar ratio of Na2O:H2O=40-90:1:4.0-15.0:500-2000 is preferably used. The silicon source, aluminum source, alkali source and water are preferably mixed in a ratio of SiO2:Al2O 3: The mixture was mixed in a molar ratio of Na2O:H2O=60:1:5.8:1500.
[0044] In some embodiments of the present invention, the amount of the pore expanding agent added in step (1) is 1 to 10 wt% of SiO2. Preferably, the amount of the pore expanding agent added is 5 wt% of SiO2.
[0045] The water used in the present invention refers to deionized water, distilled water or ultrapure water unless otherwise specified.
[0046] In some embodiments of the present invention, step (2) uses rotary evaporation to remove part of the solvent, the rotary evaporation temperature is 100-150°C, and the rotary evaporation time is 2-4 hours. Preferably, the rotary evaporation temperature is 120°C, and the rotary evaporation time is 2 hours.
[0047] In some embodiments of the present invention, the extrusion molding in step (3) is at least one of a strip, a sphere or a clover shape, a cylindrical mesoporous shape, a four-leaf clover shape, a dumbbell shape, a honeycomb shape, a wheel shape or a cross-hole cylindrical shape.
[0048] In some embodiments of the present invention, the template agent in step (4) is an amine compound. Preferably, the template agent includes at least one of pyrrolidine, ethylenediamine, cyclohexylamine and pyridine.
[0049] In some embodiments of the present invention, the concentration of the template solution in step (4) is 3-15%, preferably, the concentration of the template solution is 8%.
[0050] In some embodiments of the present invention, the solid-liquid ratio of the catalyst precursor III to the template solution in step (4) is 1:5-25. Preferably, the solid-liquid ratio of the catalyst precursor III to the template solution is 1:5.
[0051] In some embodiments of the present invention, the crystallization temperature in step (4) is 150-190° C., and the crystallization time is 48-108 h. Preferably, the crystallization temperature is 170° C., and the crystallization time is 96 h.
[0052] In some embodiments of the present invention, the system temperature during the exchange with the ammonium salt aqueous solution in step (5) is 40-90°C, and the exchange time is 1-6 hours. Preferably, the system temperature during the exchange with the ammonium salt aqueous solution is 45°C, and the exchange time is 3 hours.
[0053] In some embodiments of the present invention, the concentration of the ammonium salt aqueous solution in step (5) is 3-10 wt %. Preferably, the concentration of the ammonium salt aqueous solution is 5 wt %.
[0054] In some embodiments of the present invention, the drying conditions in the method are 100-150°C for 6-10 hours, and the roasting conditions are 450-600°C for 4-8 hours. Preferably, the drying conditions are 110°C for 10 hours, and the roasting conditions are 550°C for 6 hours.
[0055] The present invention also provides a binder-free ZSM-35 catalyst prepared according to the method and the use of the ZSM-35 catalyst in hydrocarbon conversion. Preferably, the ZSM-35 catalyst is used in olefin skeletal isomerization reaction.
[0056] The present invention does not limit the type of hydrocarbon conversion, including but not limited to isomerization, aromatization, polymerization reaction, etc.
[0057] In some embodiments of the present invention, the crystal size of the ZSM-35 catalyst is 50-500 nm.
[0058] In some embodiments of the present invention, the specific surface area of the ZSM-35 catalyst is 250-350, preferably 310. The pore volume of the ZSM-35 catalyst is 0.18-0.25, preferably 0.23.
[0059] In some embodiments of the present invention, the reaction temperature is 250-350°C, preferably 300°C, and the space velocity is 1-7h -1 , preferably 5h -1 The reaction pressure is 0.1-0.2, preferably 0.1 MPa.
[0060] The binder-free ZSM-35 catalyst prepared by the present invention has the characteristics of low reaction temperature and high selectivity in olefin isomerization reaction. -1 Under the reaction conditions, the conversion rate and selectivity are higher than 45% and 85%, respectively.
[0061] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0062] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the raw materials and auxiliary agents are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0063] Example 1
[0064] A method for preparing a binder-free ZSM-35 catalyst, the specific steps are as follows:
[0065] (1) 300.0 g of silica sol, 6.0 g of sodium aluminate, 12.0 g of NaOH and 4.5 g of polyethylene glycol were uniformly mixed to obtain catalyst precursor I;
[0066] (2) placing the catalyst precursor I in a rotary evaporator and performing rotary evaporation at 120° C. for 2 h to obtain a catalyst precursor II having a dry basis of 50%;
[0067] (3) Extruding the catalyst precursor II into a φ2 strip, drying it at room temperature, and then transferring it to a 110°C oven for drying for 10 hours to obtain a catalyst precursor III;
[0068] (4) Adding catalyst precursor III to 8% pyridine solution, transferring to a crystallization kettle at a solid-liquid ratio of 1:5, crystallizing at 170° C. for 96 h, washing with water until neutral after crystallization, drying in an oven at 110° C. for 10 h, and calcining at 550° C. for 6 h to obtain a binder-free Na-type ZSM-35 catalyst;
[0069] (5) The binder-free Na-type ZSM-35 catalyst was exchanged with a 5 wt% ammonium salt aqueous solution at 45°C for 3 h, washed with water until neutral, dried in an oven at 110°C for 10 h, and calcined at 500°C for 6 h to obtain a binder-free H-type ZSM-35 catalyst #1. The SEM image is as follows: Figure 1 .
[0070] Comparative Example 1
[0071] The difference between Comparative Example 1 and Example 1 is that the Na-type ZSM-35 molecular sieve is prepared by conventional hydrothermal synthesis process, and the H-type ZSM-35 molecular sieve is obtained by washing, drying, roasting, and exchanging with ammonium salt solution, and then a binder is added and extruded to obtain the ZSM-35 catalyst. Figure 2 .
[0072] The preparation method of the ZSM-35 catalyst described in Comparative Example 1 is as follows:
[0073] (1) H2O was added to the crystallization kettle, and NaOH and sodium aluminate were added under stirring, and the mixture was stirred evenly. After pyridine was added, the mixture was stirred for 0.5 h, and silica sol was added, and the mixture was stirred for 3 h to obtain a reaction gel. The reaction gel was prepared according to the molar ratio of SiO2:Al2O 3: Na2O:pyridine:H2O=60:1:3.5:19.0:1500;
[0074] (2) The reaction gel was transferred into an autoclave and crystallized at 170°C for 96 h;
[0075] (3) After the crystallization is completed, the Na-type ZSM-35 molecular sieve is obtained by filtering, washing, drying and calcining, wherein the calcination temperature is 550° C. for 6 hours;
[0076] (4) exchanging the Na-type ZSM-35 molecular sieve with a 5 wt % ammonium salt aqueous solution at 45° C. for 3 h, washing with water until neutral, and drying in an oven at 110° C. for 10 h to obtain the H-type ZSM-35 molecular sieve;
[0077] (5) The H-type ZSM-35 molecular sieve is uniformly mixed with 10% alumina powder and 3% nitric acid, and the mixture is extruded, dried and calcined to obtain a ZSM-35 catalyst.
[0078] The activities of the ZSM-35 catalysts prepared in Example 1 and Comparative Example 1 were evaluated.
[0079] Evaluation method: The catalyst activity test was carried out on a fixed bed reactor with a reaction pressure of 0.1 MPa. The experimental process is as follows: 4 g of catalyst (20-40 mesh) and 4 g of quartz sand (20-40 mesh) were weighed, mixed and loaded into a stainless steel reaction tube with a diameter of 10 mm. Before the reaction, the catalyst was heated to the reaction temperature under nitrogen flow and activated at this temperature for 1 h, and then 1-butene raw gas was introduced for reaction. After the reaction, samples were taken through a six-way valve every 4 hours and entered the chromatographic analysis system for online analysis, and the liquid product was analyzed offline.
[0080] Mechanical strength test: Intelligent particle strength tester (ZQJ-II, Dalian Intelligent Testing Machine Factory, China), the particle length used in the test is 3 to 5 mm.
[0081] Specific surface area and pore volume test: Physical adsorption instrument (ASAP-2460, Micromeritics, USA): The structural properties of the samples were analyzed by N2 isothermal adsorption and desorption. The samples were pretreated by vacuum degassing at 350°C for 24 hours, and the adsorption and desorption experiments were carried out at liquid nitrogen temperature (-196°C); the specific surface area of the catalyst was calculated by the Brunauer-Emmett-Teller (BET) method, the micropore specific surface area was calculated by the t-plot method, the mesopore pore size distribution was calculated by the Barret-Joyner-Halenda (BJH) method based on the N2 adsorption curve, and the micropore size distribution was calculated by the NLDFT model.
[0082]
[0083] Among them: A total : Total peak area; A 1-butene : 1-butene peak area; A cis-2-butene : cis-2-butene peak area; A trans-2-butene : Trans-2-butene peak area; A isobutene : Isobutylene peak area.
[0084] Table 1 Physical parameters and activity test results of catalysts obtained by different preparation methods, reaction conditions: T = 300 ° C, P = 0.1 MPa, space velocity 5 h -1 .
[0085]
[0086] It can be seen from Table 1 that compared with the catalyst prepared by conventional hydrothermal synthesis, the ZSM-35 molecular sieve prepared by the binderless method has the highest specific surface area, pore volume, 1-butene conversion rate and isobutylene selectivity. The above experimental results show that the binderless molecular sieve method has significant advantages, does not reduce the mechanical strength of the catalyst powder, and also improves the catalytic performance, which can be used for industrial scale-up production.
[0087] Example 2-3
[0088] The difference between Example 2-3 and Example 1 is that different silicon sources are used. The silicon sources used in Examples 2 and 3 are C-type silica gel and white carbon black, respectively. The performance evaluation results are shown in Table 2. SEM is shown in Table 2. Figure 3-4 .
[0089] Table 2 Physical parameters and activity test results of catalysts obtained from different silicon sources, reaction conditions: T = 300 ° C, P = 0.1 MPa, space velocity 5 h -1 .
[0090]
[0091] It can be seen from Table 2 that the physical parameters of the catalysts prepared from different silicon sources are not much different, and the order of isobutylene yield is: silica sol> C-type silica gel> white carbon black.
[0092] Embodiment 4-5
[0093] The difference between Example 4-5 and Example 1 is that different aluminum sources are used. The aluminum sources used in Examples 4 and 5 are aluminum nitrate and pseudo-boehmite, respectively. The performance evaluation results are shown in Table 3. SEM is shown in Figure 3-4 .
[0094] Table 3 Physical parameters and activity test results of catalysts obtained with different aluminum sources, reaction conditions: T = 300 ° C, P = 0.1 MPa, space velocity 5 h -1 .
[0095]
[0096] It can be seen from Table 3 that the physical parameters of the catalysts prepared from different aluminum sources are not much different, and the order of isobutylene yield is: sodium aluminate > aluminum nitrate > pseudo-boehmite.
[0097] Embodiment 6-7
[0098] The difference between Example 6-7 and Example 1 is that different pore-enlarging agents are used. The pore-enlarging agents used in Examples 6 and 7 are methyl cellulose and starch, respectively. The performance evaluation results are shown in Table 4. SEM is shown in Table 4. Figure 3-4 .
[0099] Table 4 Physical parameters and activity test results of catalysts obtained with different pore-enlarging agents, reaction conditions: T = 300 °C, P = 0.1 MPa, space velocity 5 h -1 .
[0100]
[0101] It can be seen from Table 4 that the physical parameters of the catalysts prepared with different pore-enlarging agents are not much different, and the order of isobutylene yield is: polyethylene glycol > starch > methyl cellulose.
[0102] Embodiment 8-9
[0103] The difference between Example 8-9 and Example 1 is that different template agents are used. The template agents used in Examples 8 and 9 are methyl cellulose and starch, respectively. The performance evaluation results are shown in Table 5. SEM is as follows: Figure 3-4 .
[0104] Table 5 Physical parameters and activity test results of catalysts obtained with different templates, reaction conditions: T = 300 ° C, P = 0.1 MPa, space velocity 5 h -1 .
[0105]
[0106] It can be seen from Table 5 that the physical parameters of the catalysts prepared with different templates are not much different, and the order of isobutylene yield is: polyethylene glycol > starch > methyl cellulose.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a binder-free ZSM-35 catalyst, characterized in that: The following steps are involved: (1) mixing a silicon source, an aluminum source, an alkali source, a pore-enlarging agent and water uniformly to obtain a catalyst precursor I; (2) removing part of the solvent from the catalyst precursor I to obtain a catalyst precursor II having a dry weight of 40 to 60%; (3) Extruding the catalyst precursor II into a shape and drying it to obtain the catalyst precursor III; (4) adding the catalyst precursor III to the template solution, and sequentially performing hydrothermal crystallization, filtering, washing, drying, and calcining to obtain a binder-free Na-type ZSM-35 catalyst; (5) The binder-free Na-type ZSM-35 catalyst is exchanged with an ammonium salt aqueous solution, washed to neutrality, dried, and calcined to obtain a binder-free ZSM-35 catalyst.
2. The method for preparing a binder-free ZSM-35 catalyst according to claim 1, characterized in that: The silicon source in step (1) includes at least one of silica sol, C-type silica gel, and white carbon black; the aluminum source includes at least one of sodium aluminate, aluminum sulfate, aluminum nitrate, pseudo-boehmite, and aluminum chloride; the alkali source includes sodium hydroxide; and the pore expanding agent includes any one of methyl cellulose, sesbania powder, polyethylene glycol, activated carbon, and starch.
3. The method for preparing the binder-free ZSM-35 catalyst according to claim 1, characterized in that: In step (1), the silicon source, aluminum source, alkali source and water are prepared according to the formula of SiO2:Al2O 3: The pore-enlarging agent is mixed in a molar ratio of Na2O:H2O=40-90:1:4.0-15.0:500-2000, and the added amount of the pore-enlarging agent is 1-10wt% of SiO2.
4. The method for preparing the binder-free ZSM-35 catalyst according to claim 1, characterized in that: The template in step (4) is an amine compound, and the template includes at least one of pyrrolidine, ethylenediamine, cyclohexylamine, and pyridine. The concentration of the template solution is 3 to 15%, and the solid-liquid ratio of the catalyst precursor III to the template solution is 1:5 to 25.
5. The method for preparing the binder-free ZSM-35 catalyst according to claim 1, characterized in that: The crystallization temperature in step (4) is 150-190° C., and the crystallization time is 48-108 hours.
6. The method for preparing the binder-free ZSM-35 catalyst according to claim 1, characterized in that: In step (5), the system temperature is 40 to 90° C. and the exchange time is 1 to 6 hours when the ammonium salt aqueous solution is used for exchange.
7. The method for preparing the binder-free ZSM-35 catalyst according to claim 1, characterized in that: In the method, the drying conditions are all at 100-150° C. for 6-10 hours, and the roasting conditions are all at 450-600° C. for 4-8 hours.
8. A binder-free ZSM-35 catalyst prepared according to the method according to any one of claims 1 to 7.
9. Use of the ZSM-35 catalyst prepared by the method according to any one of claims 1 to 7 or the ZSM-35 catalyst according to claim 8 in hydrocarbon conversion.
10. The use according to claim 9, characterized in that: The reaction temperature is 250-350℃, and the space velocity is 1-7h -1 .
Citation Information
Patent Citations
Skeleton isomerization catalyst, and preparation method and application thereof
CN109701606A
Preparation method of total crystal ZSM-35 molecular sieve and application of total crystal ZSM-35 molecular sieve in olefin isomerization reaction
CN114713278A